How Does Profit Shifting Affect the Balance of Payments? - Hebous, Shafik (IMF Working Papers; Working Paper ;, 2021)
Profit shifting by multinational enterprises-through manipulation of transfer prices of related-party trade, intragroup lending, or the location of intangibles-affects international flows, raising the question of its impact on the current account and external balances. This paper approaches this question theoretically and empirically. In theory, profit shifting distorts the components of the current account and bilateral current account balances but leaves a country's aggregate net balance unaffected. There is, however, a real effect on current account balances, because taxes are paid to different jurisdictions. Moreover-in practice-the measured current account could change, because not all transactions are equally easy to track. Our panel empirical results broadly confirm that the current account balance tends to be, on average, unaffected by profit shifting, but taking heterogeneity into account we find that both the real tax effect and mismeasurement strengthen income balances-and thus the current account-in investment hubs.